Atracao e visitacao da abelha Apis mellifera a flores de cinco tipos comerciais de meloeiro (Cucumis melo) - Fernandes, Nayanny de Sousa (2017)
The cultivated melon (Cucumis melo) plants are divided into groups in a classification called "type", according to characteristics of the fruits they produce. Being a species dependent on biotic pollination, the ability to attract pollinators is critical to the reproduction and productivity of this plant species when under agricultural cultivation. However, pollinators may visit the flowers of different types of melon differently, which can compromise pollination and fruit production. Therefore, the objective of this study was to investigate possible differences in floral characteristics that attrack pollinators, such as number of flowers, floral morphometry and color of the petals in male and hermaphrodite / female flowers in five different types of melon which may lead to differences in visitation among their flowers. The experiment was carried out during two growing seasons, in 2014 and 2015, in the Experimental Field of Pacajus, Brazil, which belongs to Embrapa Tropical Agroindustry and consisted of studies of the crop cycle, flowering period, and morphometric and colorimetric analysis of flowers in hybrids of types Yellow, Cantaloupe, Charentais, Galia and Piel de sapo. The five types of melon studied have similar general characteristics regarding the duration of the flowering cycle, number of flowers emitted, morphometry and color of these flowers. However, differences were found between the types of melon in precocity, flowering period, number of male flowers and hermaphrodites, size of floral structures related to the attraction of pollinators, such as diameter of corolla and height and diameter of the nectariferous chamber, and shade of green. It is concluded that the Cantaloupe type presents the most attractive characteristics for bees, followed by the Yellow and Galia types, while the Peil de sapo type, and especially the Charentais, are those whose sets of characteristics would be the least attractive. The ability of bees to identify and differentiate subtle differences in these patterns may evidence these desirable characteristics in flowers, making one type of melon more attractive for visits than the others. Investigations comparing flower visitation to the five melon types are needed.